2022
DOI: 10.1021/acs.iecr.2c03268
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Rare-Earth Elements Using Supported Liquid Membrane Extraction in Pilot Scale

Abstract: The use of supported liquid membrane extraction for recovery and separation of rare-earth elements (REEs) has been investigated. Experiments have been carried out using the different configurations: (1) standard hollow fiber supported liquid membrane operation (HFSLM), (2) renewal liquid membrane operation (HFRLM), and (3) emulsion pertraction technology (EPT). The experiments were performed in pilot scale using a hollow fiber module with a mass transfer surface area of 8 m2. Synthetic feed solution was used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Indeed, development of membrane separation of REEs witnessed a global contribution from LM techniques. Nevertheless, scale-up experiments were not satisfying mainly because of the problems with LM stability and efficiency while the efforts allow for a moderate optimism [144].…”
Section: Membrane Separation Techniques For Recovery Of Reesmentioning
confidence: 99%
“…Indeed, development of membrane separation of REEs witnessed a global contribution from LM techniques. Nevertheless, scale-up experiments were not satisfying mainly because of the problems with LM stability and efficiency while the efforts allow for a moderate optimism [144].…”
Section: Membrane Separation Techniques For Recovery Of Reesmentioning
confidence: 99%
“…They reported that under optimal experimental conditions, the Nd(III)/D 2 EHPA molar ratio was 1:3, which was consistent with the obtained results of computational calculations, and that the coordinated covalent bonds between Nd(III) and D 2 EHPA were formed through six oxygen atoms. The analysis of the reaction mechanism is important because, although in general, during the reaction with di-(2-ethylhexyl)phosphoric acid, each trivalent REE ion is extracted in a complex with six molecules of D 2 EHPA arranged as dimers; other stoichiometric ratios were also reported in different experimental conditions [33,34]. One of the important limitations associated with the use of D 2 EHPA/HFSLM-based separation methods is the stability/durability of the membranes.…”
Section: Recovery Of Rees With the Use Of Supported Liquid Membranesmentioning
confidence: 99%
“…A crucial step in manufacturing these devices involves utilizing highly pure REEs, often obtained through complex and nonsustainable processes. Current separation methods use liquid-phase strategies, including membrane separation techniques, electrodialysis, or acid leaching techniques. However, these approaches involve high energy consumption, long processing times, environmental concerns related to the use of chemicals, potential generation of hazardous waste, and the need for complex equipment. Moreover, these methods may not universally apply to the entire palette of rare earth elements, leading to inefficiencies and limitations in achieving comprehensive separation.…”
Section: Introductionmentioning
confidence: 99%